2020
DOI: 10.1097/md.0000000000019317
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study comparing two treatments for active venous leg ulcers

Abstract: Endovenous laser ablation (EVLA) and ultrasound-guided foam sclerotherapy (UGFS) have largely replaced traditional surgery for treatment of varicose veins (VVs) with active venous leg ulcers (VLUs), and multiple combined modes have emerged. A retrospective cohort study was performed to compare the effect of traditional surgery (high ligation and stripping followed with compression [compression plus HL-S]) to high ligation-endovenous laser ablation-foam sclerotherapy followed with compression (compression plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
2
3
0
2
Order By: Relevance
“… 23 , 24 , 43 In a randomized study involving 580 legs with GSV insufficiency, Rasmussen 43 and Lawaetz 24 found that the 5‐year occlusion rate was 25% lower in the UFGS group. These observations are consistent with several other reports on VU patients, where relapse rates in the treatment of VUs with UGFS ranged between 5% and 13% within a year, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 whereas relapse rates of studies involving EVLA were ranging between 0% and 9%. 37 , 38 , 39 , 40 In a study by Wysong et al, 41 in which 30 patients were treated with EVLA in combination with foam sclerotherapy and/or phlebectomy of incompetent tributaries, no ulcer reoccurrence was observed within a median follow‐up time of 448 days.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 23 , 24 , 43 In a randomized study involving 580 legs with GSV insufficiency, Rasmussen 43 and Lawaetz 24 found that the 5‐year occlusion rate was 25% lower in the UFGS group. These observations are consistent with several other reports on VU patients, where relapse rates in the treatment of VUs with UGFS ranged between 5% and 13% within a year, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 whereas relapse rates of studies involving EVLA were ranging between 0% and 9%. 37 , 38 , 39 , 40 In a study by Wysong et al, 41 in which 30 patients were treated with EVLA in combination with foam sclerotherapy and/or phlebectomy of incompetent tributaries, no ulcer reoccurrence was observed within a median follow‐up time of 448 days.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the use of minimally invasive endovenous interventions, including endovenous laser and foam sclerotherapy, has gained increasing attention due to the lack of open surgical incisions, the possibility to be carried out under local/tumescent anaesthesia and consequently, their lower postoperative morbidity 12,18 . So far, a large series of studies has demonstrated the efficacy of thermal and non‐thermal endovenous techniques in reflux elimination in patients with axial venous reflux 19–30 . However, comparative studies on the different types of endovenous treatments in patients suffering from VUs are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании H. Ontas не было обнаружено статистической разницы между группами РЧА и ЭВЛК (общая частота окклюзии в обеих группах составила 100%), что позволяет назвать данные методы достаточно эффективными, безопасными и обеспечивающими высокую степень окклюзии просвета сосудов [48]. Исследование 2020 г. рассматривало сравнение эффекта традиционной методики комбинированной флебэктомии (КФЭ), ЭВЛК и склеротерапии [49]. Приоритетным методом оказалось использование ЭВЛК, при котором были выше показатели скорости заживления ВТЯ, VCSS через 6 мес.…”
Section: хирургические методыunclassified
“…However, despite the diversity of available treatments, the VU healing process is difficult and prolonged. Therefore, laser therapy, specifically Low-Level Laser Therapy (LLLT), has been used as an adjuvant to conventional treatment to aid in wound tissue repair since it reduces the inflammatory process, favors recapillarization and neoformation of tissue layers, besides increasing collagen and elastic fibers in the healed area (13)(14)(15)(16) . In this perspective, some randomized studies show, through the evaluation of clinical indicators, tissue regeneration and reduction in the size of chronic lesions (vascular and diabetic) when using this type of adjuvant therapy to conventional treatment (17)(18)(19) .…”
Section: Introductionmentioning
confidence: 99%